2015
DOI: 10.1007/s10493-015-9921-4
|View full text |Cite
|
Sign up to set email alerts
|

Infestation dynamics of Brevipalpus phoenicis (Geijskes) (Acari: Tenuipalpidae) in citrus orchards as affected by edaphic and climatic variables

Abstract: Brevipalpus phoenicis (Geijskes) is a cosmopolitan and polyphagous mite that transmits important phytoviruses, such as coffee ringspot virus, passion fruit green spot virus and Citrus leprosis virus C. To characterise the dynamics of the probability and the rate of B. phoenicis infestation in response to edaphic and climatic factors, monthly inspections were performed in nine orchards in a citrus region of the State of Bahia, Brazil, for 35 months. Three fruits per plant were examined using a magnifying glass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 32 publications
2
15
0
1
Order By: Relevance
“…On the other hand, successive rain events and relative humidity levels above 83% reduce this probability. Also, reduction in available soil-water fraction and increasing insolation and photoperiod promote higher infestation rates (LARANJEIRA et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, successive rain events and relative humidity levels above 83% reduce this probability. Also, reduction in available soil-water fraction and increasing insolation and photoperiod promote higher infestation rates (LARANJEIRA et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Developmental rates are strongly influenced by temperature, relative humidity and host plant (reviewed by Childers et al., ). In general, infestation is favoured by increased photoperiod and temperature and by low relative humidity and low soil–water availability for the plants (Ferraz Laranjeira et al., ). It has been suggested that vector species have different climatic preferences and transmission specificities (for example in Mexico, B. californicus is mostly present in cooler places at higher elevations and B. yothersi at lower elevation in warmer places) may in part explain the distribution of the different viruses (Roy et al., ).…”
Section: Pest Categorisationmentioning
confidence: 99%
“…The host range of CILV-C also extends to noncitrus rutaceous (Swinglea glutinosa) and non-rutaceaous hosts. S. glutinosa often used as hedgerows or Commelina benghalensis, growing in association with Citrus in orchards, are natural hosts of CiLV-C (Le on et al, 2008) and may play a role in the epidemiology of the leprosis disease as a source of virus inoculum and by harbouring mite vector populations. Similarly, Hibiscus rosa-sinensis, Malvaviscus arboreus, Grevillea robusta and Bixa orellana, often also used as hedgerows were shown to be hosts of CiLV-C by experimental inoculation (Nunes et al, 2012) (Table 5).…”
Section: Host Rangementioning
confidence: 99%
“…Yet, this approach has been ineffective in managing the disease . In an attempt to explain this lack of efficiency, some problems have been identified, among them, the absence of proper sampling plans and incompatibility between the spatial distribution of symptomatic and mite‐infested plants …”
Section: Introductionmentioning
confidence: 99%
“…9,10 In an attempt to explain this lack of efficiency, some problems have been identified, among them, the absence of proper sampling plans and incompatibility between the spatial distribution of symptomatic and mite-infested plants. 11,12 An efficient and economically viable management plan can be established by knowing the spatial and temporal distribution of a disease. 12 However, the lack of a correlation between disease incidence and the presence of mites in plants is one of the challenges for the citrus leprosis pathosystem.…”
Section: Introductionmentioning
confidence: 99%